Review on Clinical Perspective of Multiple Substance use Disorder and its Ayurvedic Management - Dhanya, K; Jithesh, M (International Research Journal of Ayurveda & Yoga, 2024)
Background: Substance use disorder (SUD) is a condition in which there is uncontrolled use of a substance despite harmful consequences. Multiple Substance Use Disorders (MSU) include two or more substances taken together or within a short time period, either intentionally or unintentionally. This may lead to problems such as health issues, disability, failure to meet work responsibilities, and difficulties at school and home. Studies have concluded that opiates, cannabis, amphetamines, hallucinogens, inhalants, and benzodiazepines are often used in combination as well. This leads to social, academic, and occupational impairment, along with possible negative health effects. Individuals who abuse one substance are more likely to use other substances as well. Among those aged 12 or older, 61.2 million people (i.e., 21.9% of the population) used illicit drugs in the past year. Objective: To highlight the Ayurvedic clinical perspective in the management of multiple SUDs. Method: In Ayurveda, SUD may be approached by adapting the management principles of madatyaya after assessing the dosha combination as per the clinical presentation. Several combinations useful for the management of the condition, including addiction and withdrawal management, are explained. Ashtanga Lavana, Ajmodarka, Sreekandasava, and Drakshadi Kwatha are some of the medicines used internally to reduce withdrawal symptoms. Panchakarma therapies, along with yoga and Satvavajaya Chikitsa, including family therapy, have a very good outcome in managing substance withdrawal, dependence, and even inpreventing relapse. Results: By adopting the Ayurvedic principles, the outcome of MSU management may be enhanced, and the relapse may also be possible to reduced with the biopsychosocial approach. Conclusion: Evidence-based clinical studies are the need of the hour so as to prove the authenticity of such a clinical perspective explained in Ayurvedic parlance.